Dialogamos sobre valores de respeto y solidaridad - Sanchez Dedios, Maria del Carmen (2018)
The session entitled "Dialogue on values of respect and solidarity”, was developed for first grade students, in the area of communication taking into account the listening competence, includes simple messages, and was able to express their needs, interests, feelings and experiences. Listen with respect when interacting with others, showing compression of simple messages in their native language and in Spanish. The teaching of the dialogue on values was also prepared for students to strengthen and strengthen a culture and way of being and to behave based on respect for others, inclusion and democratic and supportive ideas. That is, it is essential for students to be able to take on new challenges and to actively behave, playing an active and effective role in the construction of a much more just world. In the development of the section, motivating and challenging activities were implemented that promoted the achievement of their competences where spaces were created in the classroom for the dialogue to be held and so the students commented their ideas, opinions of what was novel or what already They knew about the subject and above all respecting ideas and opinions. The constant and active participation of the students was promoted, from which the new learning was identified with what they will get new. The strategies executed were in accordance with the interests and needs that they showed.